2022
DOI: 10.1080/17461391.2022.2039781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low load exercise with and without blood‐flow restriction on microvascular oxygenation, muscle excitability and perceived pain

Abstract: This paper aimed to examine the acute effect of low-load (LL) exercise with blood-flow restriction (LL-BFR) on microvascular oxygenation and muscle excitability of the vastus medialis (VM) and vastus lateralis (VL) muscles during a single bout of unilateral knee extension exercise performed to task failure. Seventeen healthy recreationally resistance-trained males were enrolled in a within-group randomized cross-over study design.Participants performed one set of unilateral knee extensions at 20% of one-repeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…Finally, and most importantly, further research is needed to determine whether our findings can be applied to multi-joint and/or lower-limb exercises. Nevertheless, recent studies using singleleg squat (Petrick et al, 2019) and knee extension (Kolind et al, 2023) have shown that the application of BFR caused a reduction in the total number of repetitions, the magnitude of which was similar to that in the present study. We thus believe that the acute and chronic effects of BFR on muscle endurance performance and adaptations are consistent across types of exercises.…”
Section: Limitationssupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, and most importantly, further research is needed to determine whether our findings can be applied to multi-joint and/or lower-limb exercises. Nevertheless, recent studies using singleleg squat (Petrick et al, 2019) and knee extension (Kolind et al, 2023) have shown that the application of BFR caused a reduction in the total number of repetitions, the magnitude of which was similar to that in the present study. We thus believe that the acute and chronic effects of BFR on muscle endurance performance and adaptations are consistent across types of exercises.…”
Section: Limitationssupporting
confidence: 90%
“…The sample size in experiment 1 was determined by the following procedure. Initially, we estimated an effect size (Cohen's d ) in Student's paired t ‐test to be 1.5 from previous studies investigating the acute effect of BFR on the maximum number of repetitions (Farup et al., 2015; Kolind et al., 2023; Wernbom et al., 2009). Using power analysis software (G*Power v.3.1.9.6, University of Düsseldorf, Germany), the minimal sample size required for an 80% statistical power and an α error of 5% (two tailed) resulted in seven participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an interesting finding considering how RPE is elevated with increasing proximity to failure and that BFR exercise accelerates volitional fatigue in an exercise task by as much as 43%. 25 The heterogeneity of the included studies within our analyses likely produced our findings because RPE is similar (eg, near maximal) during failure training regardless of the application of BFR, 32 necessitating additional subgrouping according to repetition scheme (eg, fixed versus failure).…”
Section: Low-load Bfr Exercise Versus Low-load Non-bfr Exercise: Rpementioning
confidence: 99%
“…Because of low microvascular oxygenation, early fatigue development in local muscle is a potential barrier to muscle training with BFR. Risks associated with excessive metabolic stress prevent increases in training volume (33)(34)(35) and/or delay-onset muscle soreness (36) under the hypoxic condition. The decline in MVC force after strength training with ischemic preconditioning is of peripheral and/or central origins, such as the accumulation of lactate (37) and decline in corticospinal excitability (10).…”
Section: Discussionmentioning
confidence: 99%